High-pressure adsorption isothermal on a novel microporous material from polyethylene terephthalate plastic waste in carbon dioxide capture applications - Awaludin Martin; Erman Taer; Nasruddin Nasruddin; Nur Khotimah (Universitas Negeri Padang, 2025)
Carbon capture is a vital strategy for mitigating climate change by reducing industrial CO2 emissions. Adsorption technology using microporous material shows significant promise. However, significant challenges persist in developing cost-effective and sustainable adsorbents. This study addresses this issue by simultaneously enabling CO2 adsorption and plastic waste utilization through activated carbon derived from polyethylene terephthalate (PET). It was evaluated under isothermal conditions (27°C, 35°C, and 45°C) at pressures up to 3500 kPa. The maximum CO2 adsorption capacity was 0.21313 kg/kg at 27°C and 3504.39 kPa, demonstrating the effectiveness of PET-derived activated carbon in capturing CO2. The Toth isotherm model exhibited a strong fit with experimental data, with an R2 of more than 99%. The Clausius-Clapeyron equation yielded an adsorption heat of 2223.66 kJ/kg using the Toth fitting, and the Chakraborty-Saha-Koyama model yielded a heat of 2383.65 kJ/kg, confirming strong adsorption potential. These results underline PET waste as a viable precursor for sustainable carbon capture adsorbents. Furthermore, the results provide essential data for developing numerical models to optimize adsorption-based carbon capture technologies.